Unraveling the relationships of phthalate exposure, long-term trajectories for novel insulin resistance biomarkers and accelerated pubertal onset in children - Jieyu Liu; Di Gao; Yanhui Li; Manman Chen; Xinli Song; Yi Zhang; Jianuo Jiang; Ruolin Wang; Ziqi Dong; Li Chen; Yang Qin; Zhiying Song; et al. (Ecotoxicology and Environmental Safety, 2025)
Phthalates (PAEs) exposure and triglyceride-glucose (TyG) index—an indicator of insulin resistance (IR), remains not fully understood. To investigate the predictive and mediating role of IR markers in associations between PAEs exposure and puberty initiation, adjusting for sex hormones. A cohort was implemented in May 2017-October 2020. Urinary creatinine-adjusted PAE levels were measured at baseline. IR surrogates including TyG, TG/HDL-c, the metabolic score for IR (METS-IR) and TyG-BMI, sex hormones were measured at multiple visits. Early puberty onset was defined as occurring at an age below the first quartile age specific to age and sex. Group-based multi-trajectory modeling was performed to identify longitudinal patterns of IR surrogates and sex hormones. Multinomial logistic regressions were used to analyze the relations among PAEs exposure, IR surrogates’ trajectories and earlier pubertal onset. Th mediating effects of IR surrogates’ trajectories was performed by mediation analyses. Of 800 children, 88.88 % initiated puberty. PAEs exposure significantly increased the risk of larger trajectories of IR surrogates and earlier puberty, while the “largest” trajectories for METS-IR (OR=2.74, 95 %CI=1.22, 6.14) and TyG-BMI (OR=2.85, 95 %CI=1.28, 6.38) could increase the odds of early pubertal onset, and had a stronger predictive ability than TyG or BMI alone. METS-IR and TyG-BMI exhibited significant mediating effects of associations between PAEs exposure and early pubertal onset with the mediating proportions of 24.17 % and 29.0 %. Trajectories of METS-IR and TyG-BMI mediated the relationship of PAEs exposure—earlier pubertal initiation independent of sex hormones. Reducing PAEs and screening IR markers are crucial for pubertal health.